Semimechanistic Modeling to Guide Venetoclax Coadministration with Ritonavir and Digoxin - Ali A. Alhadab; Ahmed Hamed Salem; Kevin J. Freise (Wiley, 2020)
Venetoclax is a cytochrome P450, family 3, subfamily A (CYP3A) substrate and was shown to inhibit P‐gp efflux transporters in vitro. To quantify the impact of CYP3A inhibition by ritonavir on venetoclax disposition and P‐gp inhibition by venetoclax on digoxin pharmacokinetics, two semimechanistic drug‐drug interaction (DDI) models of venetoclax were developed using clinical data from healthy volunteers who received subtherapeutic doses of venetoclax with ritonavir 50-100 mg or digoxin 0.5 mg. These models were then used to assess the magnitude of interaction at therapeutic venetoclax doses and to explore various clinical dosing strategies that maintain venetoclax and digoxin concentrations within their respective therapeutic windows. Simulations demonstrated that venetoclax dose reductions of at least 75% are needed when venetoclax is coadministered with ritonavir and administering digoxin at least 2 hours before venetoclax would minimize DDI. Semimechanistic modeling leveraging clinical data is a plausible approach to predict DDI and propose dose adjustments, and administration time of interacting drugs.